(untitled) (Innovative Technologica: Methodical Research Journal, 2023)
In this article, a technological analysis of machines for cleaning seed cotton from large and small impurities was made. Various methods of cleaning seed cotton from large and small impurities, existing modern machines and their advantages were considered and conclusions were drawn based on analytical data.